2021
DOI: 10.3892/ijo.2021.5211
|View full text |Cite
|
Sign up to set email alerts
|

Potential of the tumor‑derived extracellular vesicles carrying the miR‑125b‑5p target TNFAIP3 in reducing the sensitivity of diffuse large B cell lymphoma to rituximab

Abstract: Diffuse large B-cell lymphoma (DLBCL) is the most common and aggressive form of non-Hodgkin's lymphoma. Extracellular vesicles (EVs) derived from cancer cells are known to modify the tumor microenvironment. The aim of the present study was to investigate the role of miR-125b-3p carried by EVs in DLBCL in vitro and in vivo. TNFAIP3 expression in patient lesions was measured and the upstream miR that regulates TNFAIP3 was predicted using the starBase database. EVs were isolated from DLBCL cells and identified. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…NFκB interacts with the corresponding DNA sites, which can regulate the expression of related target genes (such as TNFAIP3 protein). The TNFAIP3 protein then inhibits the phosphorylation of IκB via multiple different mechanisms, 6 Disease Markers thereby increasing the IκB content, which in turn inhibits NFκB activity [6,7]. This experimental study revealed that the NFκB protein expression was vastly increased in CRC cells and significantly lower in normal adjacent tissues.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…NFκB interacts with the corresponding DNA sites, which can regulate the expression of related target genes (such as TNFAIP3 protein). The TNFAIP3 protein then inhibits the phosphorylation of IκB via multiple different mechanisms, 6 Disease Markers thereby increasing the IκB content, which in turn inhibits NFκB activity [6,7]. This experimental study revealed that the NFκB protein expression was vastly increased in CRC cells and significantly lower in normal adjacent tissues.…”
Section: Discussionmentioning
confidence: 75%
“…NF κ B interacts with the corresponding DNA sites, which can regulate the expression of related target genes (such as TNFAIP3 protein). The TNFAIP3 protein then inhibits the phosphorylation of I κ B via multiple different mechanisms, thereby increasing the I κ B content, which in turn inhibits NF κ B activity [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exosomal miR-7-5p and miR-425-5p, derived from bone marrow mesenchymal stem cells (BM-MSCs), were confirmed to inhibit proliferation, and promote apoptosis of AML cells by targeting PI3K/AKT/mTOR signaling pathway and Wilms tumor 1-associated protein (WTAP), respectively [ 209 , 210 ]. Exosomal miR-125-5p reduced sensitivity of DLBCL cells to rituximab treatment [ 211 ], while increased levels of exosomal miR-99a-5p and miR-125b-5p in sera samples of DLBCL patients were associated with shorter PFS data [ 212 ]. In MM patients, down-regulation of four exosomal miRNAs (miR-5a-5p, miR-16-5p, miR-17-5p and miR-20a-5p) was registered in the bortezomib resistance group [ 207 ], and high levels of exosomal miR-1305 indicated poor OS [ 213 ].…”
Section: Clinical Applications Of Mirnas Focusing On Hematological Ma...mentioning
confidence: 99%
“…This model would explain the clinical efficacy of Brentuximab vedotin also in cases of lack of the targeting antigen on tumor cells. In the same way, DLBCL EVs carrying miR-125b-5p can reduce tumor sensitivity to rituximab by inhibiting TNFAIP3 expression and reducing CD20 expression ( 117 ). Whether the miR-125b-5p/TNFAIP3 axis can be used as a therapeutic approach for increasing DLBCL sensitivity to anti-CD20 antibodies requires further investigations.…”
Section: Disrupting the Ev “Remote Communication” To Improve Lymphoma Prognosismentioning
confidence: 99%